2018
DOI: 10.1038/s41598-018-19846-5
|View full text |Cite
|
Sign up to set email alerts
|

Surface temperatures in New York City: Geospatial data enables the accurate prediction of radiative heat transfer

Abstract: Despite decades of research seeking to derive the urban energy budget, the dynamics of thermal exchange in the densely constructed environment is not yet well understood. Using New York City as a study site, we present a novel hybrid experimental-computational approach for a better understanding of the radiative heat transfer in complex urban environments. The aim of this work is to contribute to the calculation of the urban energy budget, particularly the stored energy. We will focus our attention on surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In Figure 5 we demonstrate the use of time-dependent broadband infrared imaging to study thermographic envelopes of large numbers of buildings in the city skyline. In par-ticular, not only are efficiency characteristics such as heat leaks and thermal couplings detectable [134,135], but the figure also shows that individual HVAC vent duty cycles can be seen at a distance as well. In ongoing and future work we are applying signal processing techniques (e.g., changepoint detection and/or Hidden Markov Models) on these infrared "sources" to extract on and off transitions much like we have done in the broadband visible imaging case [75].…”
Section: Building Thermography At Scalementioning
confidence: 93%
“…In Figure 5 we demonstrate the use of time-dependent broadband infrared imaging to study thermographic envelopes of large numbers of buildings in the city skyline. In par-ticular, not only are efficiency characteristics such as heat leaks and thermal couplings detectable [134,135], but the figure also shows that individual HVAC vent duty cycles can be seen at a distance as well. In ongoing and future work we are applying signal processing techniques (e.g., changepoint detection and/or Hidden Markov Models) on these infrared "sources" to extract on and off transitions much like we have done in the broadband visible imaging case [75].…”
Section: Building Thermography At Scalementioning
confidence: 93%
“…Their result shows that the portion of New York City they observed predominantly uses relatively inefficient high pressure sodium lamps (Dobler et al, 2016). Similar techniques have been deployed to determine New York City's refrigerant use patterns (Ghandehari et al, 2017) and thermal analysis of the built environment (Ghandehari, Emig, & Aghamohamadnia, 2018).…”
Section: The Rise Of City-scale Urban Sustainability Researchmentioning
confidence: 94%
“…City policy-makers can extrapolate this finding to the rest of the city or commission additional research to identify energy efficiency options. Refrigerant use patterns and thermal analysis of the built environment could reveal similar improvement potentials by, for instance, identifying heat losses (Ghandehari et al, 2017;Ghandehari et al, 2018).…”
Section: Urban Sustainability Research Contributions To New York Citymentioning
confidence: 99%
“…The results demonstrated that a 50 % increase in tree volume induced a 10% decrease in mean radiant temperature (MRT). Ghandehari et al [9] estimated the urban radiant heat transfer based on hyperspectral imaging of building blocks in Manhattan, New York. The study also introduced a geospatial radiosity model to describe the physical processes of LWR heat exchange between buildings.…”
Section: Introductionmentioning
confidence: 99%